Veterinary neurology residency training in Europe—A survey on preparation and plans - Gonçalves, Rita (Frontiers in Veterinary Science, 2024)
IntroductionDifficulties in recruitment of veterinary specialists to academia is an ongoing problem for university teaching hospitals. The aim of this study was to determine the proportion of veterinary neurology specialists that plan to work in academia after their residency training and identify the main factors that may influence that decision.MethodsAn electronic survey was distributed to European College of Veterinary Neurology (ECVN) residents in training and those that completed their residencies within the previous 12 months.ResultsDespite similar numbers of residents training in clinical practice and academic institutions, most respondents (79.7%) planned to work in private practice. The most influential factors for deciding future workplace were quality of life, salary, location, and the number of other specialists (with specialists in subjects other than neurology viewed as more important than neurologists) working in the same institution. The most common reasons for not choosing academia were low compensation, excessive bureaucracy, and high administrative workload compared to private clinical practice.DiscussionAcademic institutions need to review support for academic staff and provide stronger mentorship to overcome these problems and ensure provision of high-quality undergraduate teaching in veterinary neurology as well as promoting advancement of the field through basic and applied research.